1997
DOI: 10.1097/00001756-199712220-00020
|View full text |Cite
|
Sign up to set email alerts
|

Strong expression of GFAP mRNA in rat hippocampus after a closed-head injury

Abstract: We investigated the spatiotemporal GFAP mRNA expression over a period of 11 days following brain injury in rats caused by impact acceleration, which is known to produce diffuse axonal injury (DAI). We observed widespread GFAP mRNA expression throughout the brain, which was more rapid and intense in the hippocampus. This expression was obvious in most animals 2 days after injury and appeared maximal at day 6. Although it decreased by day 11, the level of expression remained high compared with control levels. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Reactive astrocytes had a distinct morphology characterized by an enlarged cell body and long intertwined processes. Our findings were consistent with Bodjarian et al 's study, in that they demonstrated increased GFAP mRNA expression after closed head injury where more intense and rapid expression was noted in the hippocampus 20…”
Section: Discussionsupporting
confidence: 93%
“…Reactive astrocytes had a distinct morphology characterized by an enlarged cell body and long intertwined processes. Our findings were consistent with Bodjarian et al 's study, in that they demonstrated increased GFAP mRNA expression after closed head injury where more intense and rapid expression was noted in the hippocampus 20…”
Section: Discussionsupporting
confidence: 93%
“…Several markers or changes in human brain tissue after traumatic brain injury have been investigated using immunohistochemistry [28, 61,62,63,64,65,66,67,68,69]. In experimental brain injury models, the detection of several different markers has been reported from between 1 h to 1 day after injury [70,71,72,73,74,75]. DAI can be found in cases that sustained mild traumatic brain injury with no macroscopic changes at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…A possible source of error in estimating NAA reduction at later time points is possible change in nonneuronal protein due to posttraumatic glial hypertrophy and invasion. Nevertheless, in this model of trauma, with no secondary insult, these phenomena are of limited importance in accounting for a 50% NAA reduction at 48 h (Bodjarian et al, 1997;Dietrich et al, 1999;Ito et al, 1996).…”
Section: N-acetylaspartate Reduction After Traumatic Brain Injurymentioning
confidence: 98%